Saúde mental e pandemia: avaliação dos níveis de ansiedade e depressão em pessoas que tiveram covid- 19 no município de Sobral-Ce. - Monte, Francisco Thiago Paiva (2023)
Considered as an acute respiratory infection caused by the SARS-CoV-2 coronavirus, Covid-19 originated in China in December 2019, with the first case of infection in Brazil being registered in February 2020. In March of the same year, the World Health Organization (WHO) characterized the Covid-19 outbreak as a pandemic, declaring it the largest international public health emergency ever faced. Emerging evidence points to the traumatic impacts on mental health, resulting in high cases of anxiety and depression in the general population, substantially caused by the numerous changes faced in the course of the Covid-19 pandemic. Thus, the present study aimed to verify the levels of anxiety and depression in people affected by Covid-19. A cross-sectional, exploratory, descriptive quantitative research was carried out. The study sample consisted of 320 people. The inclusion criteria were people who had a positive diagnosis of Covid-19 between March 2020 and January 2021, being over 18 years old, living in the municipality of Sobral-CE and signaling acceptance in the Free and Informed Consent Form. Data collection took place between October and December 2022 and was carried out online. For this purpose, a sociodemographic questionnaire, the Patient Health Questionnaire (PHQ-9) and the Generalized Anxiety Disorder Questionnaire (GAD-7) were used. The research followed the ethical assumptions of the National Health Council and was approved by the Research Ethics Committee of the Instituto Superior de Teologia Aplicada-INTA, having been approved with Opinion No. 4,303,812 and CAAE: 36913220.8.0000.8133. The data were analyzed with the support of the Statistical Package for the Social Sciences (IBM SPSS), version 22.0 for Windows®, and multiple linear regression analyses were performed. The majority of respondents were female (71.9%), aged between 18 and 68 years, 75.6% had an income of up to three minimum wages, 54.1% were single and 35.9% were married, and most self- declared as brown (58.4%), followed by white (30.3%). The results revealed that half of the sample had moderate to severe levels of depression (50.6%) and 41.2% of participants had moderate to severe anxiety scores. In this sense, in view of the measurement of the data collected, statistically significant and with higher rates of anxiety and depression were women, young adults, people with some comorbidity, who did not work during the pandemic, who did not practice physical and leisure activities and those with a history of drug treatment for mental health. This study favored the quantification of anxiety and depression levels in the study population, as well as the identification of the main predictors for the development of symptoms, revealing some specific and more vulnerable audiences for both. In view of the above, there is a need to develop care strategies to be implemented, in order to contemplate new perspectives of care, with a view to fostering the improvement of mental well-being and the timely reception of demands in the post-pandemic period.